2022
DOI: 10.1109/tse.2020.3025317
|View full text |Cite
|
Sign up to set email alerts
|

Real World Scrum A Grounded Theory of Variations in Practice

Abstract: Scrum, the most popular agile method and project management framework, is widely reported to be used, adapted, misused, and abused in practice. However, not much is known about how Scrum actually works in practice, and critically, where, when, how and why it diverges from Scrum by the book. Through a Grounded Theory study involving semi-structured interviews of 45 participants from 30 companies and observations of five teams, we present our findings on how Scrum works in practice as compared to how it is prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 31 publications
0
22
0
4
Order By: Relevance
“…For the development and implementation of this research work, the Scrum methodology was selected, this methodology is positioned among the best methodologies known worldwide, it is focused on software development, this methodology offers a suitable way to comply with good practices, before collaborative work giving the possibility of giving the best results in the projects, providing security and viability towards its final goal. On the other hand, the main characteristics of this methodology are based on its speed, adaptability, efficiency and flexibility [12]. It also has the guarantee of obtaining an environment, with security and transparency, having an environment of continuous progress, without loss of resources as it is a methodology prepared to change regardless of its difficulty [13].…”
Section: A Scrum Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…For the development and implementation of this research work, the Scrum methodology was selected, this methodology is positioned among the best methodologies known worldwide, it is focused on software development, this methodology offers a suitable way to comply with good practices, before collaborative work giving the possibility of giving the best results in the projects, providing security and viability towards its final goal. On the other hand, the main characteristics of this methodology are based on its speed, adaptability, efficiency and flexibility [12]. It also has the guarantee of obtaining an environment, with security and transparency, having an environment of continuous progress, without loss of resources as it is a methodology prepared to change regardless of its difficulty [13].…”
Section: A Scrum Methodologymentioning
confidence: 99%
“…The second stage is the implementation stage, which focuses on creating, estimating and identifying the user stories (HU) that were previously collected as requirements. Also, after that, the Sprint is determined, which is the time in which the project deliverables will be developed and, finally, the product backlog is created [12].…”
Section: A Scrum Methodologymentioning
confidence: 99%
“…Transition Practice Role Key focus/Insight Masood et al (2020b) x Shows how Scrum works in practice as compared to how it is presented in its formative books. The authors identified significant variations when comparing the formative descriptions and the "real world setting" Shastri et al (2021a) x x Highlights the continued presence of the role of the project manager in Agile software projects as a part of the transition from traditional to Agile ways of working Shastri et al (2021b) x x Presents and describes the Scrum master's role in Agile projects and find a positive association between the presence of the Scrum master and the frequency with which Agile practices are carried out by the team Table 2.…”
Section: Authormentioning
confidence: 99%
“…Kaizen does not claim external validity [12] and adopting it requires the users to adapt it to their context for the same reasons that companies tailor methods (including Scrum) to fit their values, culture, reality, needs, and strategies [7], [1].…”
Section: B Data Collection Proceduresmentioning
confidence: 99%